An ARXPS and ERXPS study of quaternary ammonium and phosphonium ionic liquids: utilising a high energy Ag Lα′ X-ray source. Issue 8 (5th February 2016) - Blundell, Rebecca K.; Delorme, Astrid E.; Smith, Emily F.; Licence, Peter
Abstract : A series of ammonium- and phosphonium-based ionic liquids have been probed using X-ray photoelectron spectroscopy (XPS) with a high energy Ag Lα′ X-ray source. Abstract : A series of ammonium- and phosphonium-based ionic liquids have been probed using X-ray photoelectron spectroscopy (XPS) with a high energy Ag Lα′ X-ray source. The capability of the Ag Lα′ X-ray source for ionic liquid analysis is confirmed alongside the characterisation of previously undetected high energy core photoelectron emissions. Additionally, the utilisation of the Ag Lα′ X-ray source as a depth profiling technique (ERXPS) to investigate the structure of the ionic liquid/vacuum interface has been demonstrated, with comparison made to angle resolved X-ray photoelectron spectroscopy (ARXPS).